Bladder Instillations With Triamcinolone Acetonide for Interstitial Cystitis–Bladder Pain Syndrome: A Randomized Controlled Trial. Issue 5 (May 2021) - Cardenas-Trowers, Olivia O.; Abraham, Alyce G.; Dotson, Thomas K.; Houlette, Brooke A.; Gaskins, Jeremy T.; Francis, Sean L.
Abstract : OBJECTIVE: To evaluate the utility of adding triamcinolone acetonide to a standard bladder instillation solution for treatment of interstitial cystitis–bladder pain syndrome. METHODS: This was a single-center, randomized, double-blind trial that compared symptom response in women with interstitial cystitis–bladder pain syndrome who underwent six bladder instillations with triamcinolone acetonide or six instillations without. All instillation solutions contained heparin, viscous lidocaine, sodium bicarbonate, and bupivacaine. The primary outcome was the change in interstitial cystitis–bladder pain syndrome symptoms from the first to sixth bladder instillation between groups based on the total OLS (O'Leary-Sant Questionnaire) score. Assuming a 4.03-point or larger difference in the mean total OLS score from the first to sixth bladder instillation as compared between the groups, 64 participants were needed to show a significant difference with 80% power at the 0.05 significance level. RESULTS: From January 2019 to October 2020, 90 women were enrolled—45 per group; 71 (79%) completed all six bladder instillations. Randomization resulted in groups with similar characteristics. There was no difference between groups in the primary outcome (bladder instillation with triamcinolone acetonide: mean OLS change −6.7 points, 95% CI 4.6–8.8 and bladder instillation without triamcinolone acetonide: mean OLS change −5.8 points, 95% CI 3.4–8.1; P =.31). Women in both groups had improvement in their interstitial cystitis–bladder pain syndrome symptoms as indicated by a decrease in the total OLS score from the first to sixth bladder instillation. CONCLUSION: The addition of triamcinolone acetonide to a standard bladder instillation solution does not improve symptoms associated with interstitial cystitis–bladder pain syndrome. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03463915. Abstract : The addition of triamcinolone acetonide to standard bladder instillation solution does not improve symptoms associated with interstitial cystitis–bladder pain syndrome.